Copper(II) Anchored on Amine-Functionalized MMT: A Highly Efficient Catalytic System for the One-Pot Synthesis of Bispyrano[2,3-c]pyrazole Derivatives - Majid Ahmadzadeh; Masoud Sadeghi; Javad Safari (Journal of Chemistry)
In this study, preparation of pyridine-2-carboimine copper complex immobilized on amine-functionalized nanoclay montmorillonite K10 was reported. The products were characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and thermogravimetric analysis (TGA). The catalytic activity of this new nanocatalyst, as a natural, renewable, inexpensive, and heterogeneous catalyst, was very effective for the four-component condensation reaction of hydrazine hydrate (or phenyl hydrazine), malononitrile, β-ketoester, and terephthalaldehyde (or isophthalaldehyde) toward the synthesis of multisubstituted bispyrano[2,3-c]pyrazole derivatives. From the viewpoint of green chemistry, the advantages of this approach are accessibility, simplicity, and high yields synthesis. The catalyst was recycled and reused four times without significant loss of activity.